DISTAL SCAPHOID RESECTION ARTHROPLASTY FOR SCAPHOID NONUNION WITH RADIOSCAPHOID ARTHRITIS - Drac, Pavel; Manak, Pavel; Pieranova, Lucie (Biomedical papers, 2006)
The authors compare the functional outcome of 8 patients treated by distal scaphoid resection arthroplasty for scaphoid nonunion with symptomatic wrist arthritis before surgery and after a minimum follow-up of 6 months. There was a significantly better range of radial deviation and grip strength at the time of re-examination. Significantly fewer patients complained of resting pain. By contrast the change of radiolunate angle measured before the surgery and at the time of re-examination was statistically insignificant. Our preliminary results show that distal scaphoid resection arthroplasty seems to be a useful treatment method of scaphoid nonunion with symptomatic wrist arthritis.
Keywords: Scaphoid nonunion/Radioscaphoid arthritis/Distal scaphoid resection arthroplasty